1993
DOI: 10.1126/science.7678352
|View full text |Cite|
|
Sign up to set email alerts
|

Carbon Monoxide: a Putative Neural Messenger

Abstract: Carbon monoxide, an activator of guanylyl cyclase, is formed by the action of the enzyme heme oxygenase. By in situ hybridization in brain slices, discrete neuronal localization of messenger RNA for the constitutive form of heme oxygenase throughout the brain has been demonstrated. This localization is essentially the same as that for soluble guanylyl cyclase messenger RNA. In primary cultures of olfactory neurons, zinc protoporphyrin-9, a potent selective inhibitor of heme oxygenase, depletes endogenous guano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
971
1
10

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,490 publications
(1,007 citation statements)
references
References 35 publications
25
971
1
10
Order By: Relevance
“…Other free radicals may function in this way, like carbon monoxide (see Verma et al, 1993). Another potential new group is the polyamines which can be released from postsynaptic cells in a Ca 2+ dependent manner and can modulate presynaptic transmitter release (Bondy and Walker, 1986;Fage et al, 1992).…”
Section: Other Messengersmentioning
confidence: 99%
“…Other free radicals may function in this way, like carbon monoxide (see Verma et al, 1993). Another potential new group is the polyamines which can be released from postsynaptic cells in a Ca 2+ dependent manner and can modulate presynaptic transmitter release (Bondy and Walker, 1986;Fage et al, 1992).…”
Section: Other Messengersmentioning
confidence: 99%
“…Since NOS is a hemoprotein, CO is able to bind to the existing NOS and inactivate the molecule. Conversely, NO could modulate HO-2 activity through free radical attack on ÀSH groups on HO-2 (Verma et al, 1993;Maines, 1997;Juckett et al, 1998). Ischiropoulos et al (1996) have found that CO exposure leads to the perivascular accumulation of nitrotyrosine, a marker of peroxynitrite (OONO À ) production.…”
Section: Discussionmentioning
confidence: 99%
“…HO-3 is a recently identified isoform and appeares to regulate heme-dependent genes (Magnusson et al, 2000). CO, like nitric oxide (NO), binds to the heme moeity of soluble guanylate cyclase (sGC) (Brune et al, 1990;Verma et al, 1993;Ingi et al, 1996a;Snyder et al, 1998) and in cultured olfactory neurons HO inhibitors reduce cGMP levels (Ingi et al, 1996b). Cytochrome c oxidase, the terminal enzyme in the mitochondrial electron transport chain, is another potential target for the actions of CO in the cell (Piantadosi, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…10a). CO acts as an agonist to soluble gunanylate cyclase similar to NO, and can also result in the formation of cGMP (Verma et al, 1993). Our early expectation was that CO exposure would result in an increase in cGMP.…”
Section: The Co/no-cgmp Pathway Is Important For Neuronal Migrationmentioning
confidence: 97%